Blood utilization in liver transplantation (BUILT): A multidisciplinary survey of transfusion practices. Issue 1 (14th November 2022) - DeSimone, Robert A.; Hess, Aaron S.; Rajendran, Pranesh; Tanaka, Kenichi A.; Cushing, Melissa M.; Eichbaum, Quentin
Abstract: Background: The purpose of this study was to survey liver transplant centers in the United States to assess baseline practices in blood utilization and identify opportunities for standardization to optimize blood use in these complex cases. Study Design and Methods: Two surveys, one for transfusion medicine physicians and the other for anesthesiologists, were distributed to high‐volume liver transplant centers. Results: The response rate was 52% for both surveys. The majority of respondents (90%) indicated they issue a standardized number of blood products to start surgeries. The most common number of products issued before the start of cases were 10 red blood cells (RBC) and 10 plasma units with no platelets or cryoprecipitate. On average, fewer RBC (7.5) and plasma (7) units were transfused than issued. Decisions to transfuse RhD+ RBCs to RhD‐ patients and use antigen untested units in alloimmunized patients were mainly handled on a case‐by‐case basis. Many centers reported utilizing viscoelastic testing (97%) and cell salvage (97%). Most centers reported standardized, laboratory‐based intraoperative transfusion goals for RBCs (65%) and fibrinogen replacement (52%) but lacked a standardized approach for plasma (55%) and platelets (58%). Discussion: More blood products are issued during surgery than are transfused. Responses from anesthesiology providers suggest a broad consensus on practice. Almost all respondents use viscoelastic testing in the management of intraoperative coagulopathy, either alone or in combination with classical coagulation tests. The majority of programs do not transfuse clotting factor concentrates, including fibrinogen concentrate, prothrombin complex concentrates, and recombinant activated FVII, and do not use antifibrinolytics prophylactically.